2000
DOI: 10.1046/j.1365-2958.2000.02037.x
|View full text |Cite
|
Sign up to set email alerts
|

Entamoeba histolytica cysteine proteinases with interleukin‐1 beta converting enzyme (ICE) activity cause intestinal inflammation and tissue damage in amoebiasis

Abstract: SummaryThe protozoan parasite Entamoeba histolytica causes intestinal inflammation and ulceration. Amoebic trophozoites activate the transcription factor NF-kB in human intestinal epithelial cells, initiating an inflammatory response programme with resultant damage to the intestinal tissue. Amoebic cysteine proteinases have been proposed as important virulence factors for amoebiasis. To test the role of amoebic cysteine proteinases in the pathogenesis of amoebic colitis, human intestinal xenografts in SCID mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
1
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(94 citation statements)
references
References 23 publications
(48 reference statements)
1
90
1
2
Order By: Relevance
“…On the other hand, pathogenic protozoa have shown to cause intestinal inflammation and tissue damage,17, 18 which have shown to exacerbate the systemic inflammatory process 19…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, pathogenic protozoa have shown to cause intestinal inflammation and tissue damage,17, 18 which have shown to exacerbate the systemic inflammatory process 19…”
Section: Introductionmentioning
confidence: 99%
“…Stuck to the trophozoites mucosa secrete specific proteolytic enzymes such as hyaluronidase, cysteine proteinase, cathepsin B, which produce a local inflammatory reaction, congestion, degradation attacked by amoeba cells and facilitate trophozoites further invasion of the intestinal submucosa tissue [13,18,21,23]. Trophozoites of amoeba cause induction of the enzyme cyclooxygenase-2 (COX-2) in the lining of the bowel, leading to an increase in the secretion of prostaglandin E 2 (PGE 2 ), which contributes to the stimulation of the inflammatory process [24].…”
Section: Pathophysiology and Clinical Signs Of Infestationmentioning
confidence: 99%
“…The antisense approach has been applied to E. histolytica cysteine proteinases and episomal expression of an antisense RNA to ehcp5 could reduce total amoebic proteinase activity by 80-90% [Ankri et al 1998]. To assess the role of E. histolytica cysteine proteinases in amoebiasis, in earlier study, human xenografts in SCID-HU-INT mice were infected with amoebic trophozoites expressing the ehcp5 antisense RNA(proteinase-deficient amoebae) or amoebic trophozoites containing the same plasmid without the antisense insert (the control group) [Zhang et al 2000]. Major findings were: 1. no obvious defect was apparent in the ability of cysteine-proteinase deficient amoebae to inhabit and survive within the colonic lumen; 2. post-24 h after infection, cysteine proteinase-deficient amoeba had, in contrast to the control group, failed to induce significant amounts of human IL-1 or IL-8 from infected intestine; 3. gut inflammation was also reduced in human intestine infected with cysteine-proteinase-deficient E. histolytica trophozoites; 4. control E. histolytica trophozoites damaged the intestinal permeability barrier at 24 h but there was only a minimal increase in intestinal permeability in human intestinal xenografts infected with cysteine-protease-deficient amoeba; 5. histological studies at 24 h, human xenografts infected with control amoebae showed damage to the colonic mucosa, invasion of amoebic trophozoites into submucosal tissues and neutrophil-predominant inflammation; 6. by contrast, xenografts infected with cysteine-proteinase-deficient amoebae showed less mucosal damage, almost no evidence for amoebic invasion into submucosal tissue and little inflammation.…”
Section: Mechanisms Of Hepatocellular Dysfunction and Regeneration: Ementioning
confidence: 99%